Successful treatment of pancreatitis caused by L-asparaginase in clinical practice - Yu. S. Korkina; M. A. Shervashidze; T. T. Valiev; N. A. Batmanova; T. R. Panferova (Онкогематология, 2024)
Treatment intensification of acute lymphoblastic leukemia in children with L-asparaginase (L-ASP) improves therapy effectiveness and shows high survival rates. The unique biological properties of this enzyme make it possible to suppress tumor blasts proliferation by reducing blood asparagine concentration. L-ASP use is limited by toxicity and hypersensitivity reactions observed in 75 % of cases. Although most complications during L-ASP therapy are mild/moderate and are manageable with adequate accompanying therapy, the development of severe side effects leads to forced withdrawal of L-ASP, which significantly reduces the likelihood of a favorable outcome in children with acute lymphoblastic leukemia. One of the most severe toxicity manifestations is the development of asparaginase-associated pancreatitis. It worsens the prognosis and may cause patients’ death. This article presents both current data about asparaginase-associated pancreatitis and treatment experience of this complication at the Research Institute of Pediatric Oncology and Hematology of the N. N. Blokhin National Research Center of Oncology.